Feasibility of promoting neighbourhood food centres to tourists. - Kho, Pei Ling. (2008)
The purpose of this project is to find out the feasibility of promoting neighbourhood food centres to tourists, which is a reflection of the true Singapore. The research findings show that neighbourhood food centres do have the potential to attract tourists. Perhaps, this will be the start of exposing Singapore's own version of alfresco dining to tourists.